TINGKAT PENCAPAIAN TARGET DAN EFISIENSI PENDAPATAN ASLI DAERAH (PAD) KOTA SALATIGA - Ika Kristianti; Berliana Dara Jati (Dinamika Akuntansi Keuangan dan Perbankan, 2019)
This study aims to determine the level of achievement of taxes and levies, local tax efficiency, and contributes taxes and levies on Salatiga’s local revenue. This research uses descriptive quantitative method. The technique of collecting data through interviews, observation, and documentation. The data used is data relating to the realization of taxes and levies, budgets of local taxes and levies, as well as Salatiga’s local revenues. The data analysis used in this research is the analysis of the level of achievement of taxes and levies, local tax efficiency analysis, and analysis of the contribution of taxes and levies. Results of the study are: (1) The level of achievement of targets for local taxes and levies during the years 2011-2015 in the category very effective. (2) The efficiency rate for local taxes and levies from 2011-2015 as a whole are at an efficient level. (3) The contribution of local taxes on Salatiga’s revenue from 2011 until 2015 less contribute. Keywords: local taxes, levies, local revenues, the level of achievement of targets, efficiency, contribution.